Paulo Freire's Contributions to Women's Empowerment in the countryside (Research, Society and Development, 2020)
Women's empowerment is a current topic that addresses gender relations. This article aims to analyze Paulo Freire's contributions to female empowerment in the countryside to build an egalitarian peasant society in gender relations. For the explanation of the theme, the text is divided into three topics: Progressive Pedagogy and Gender Relations; Peasant Female Empowerment in a Freirean Perspective and Labor Relations between Genders in the field. The methodology used is bibliographic research. Empowerment, according to Paulo Freire, is not enough for social transformation, but it is an important movement, and thus, as a process of social transformation. Empowered women are social and emancipated subjects. Able to perceive, reflect and interpret their social reality in the sense of individually and / or collectively, produce significant changes for the construction of a more humane and democratic society.